2017
DOI: 10.1016/j.ijproman.2017.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Do prior interactions breed cooperation in construction projects? The mediating role of contracts

Abstract: There has long been inconsistence on the relationship among prior interactions, contracts and cooperative behavior. This study aims to examine how prior interactions affect cooperative behavior, including the effects of prior interactions on cooperative behavior and the mediating role of the contract between prior interactions and cooperative behavior. We classify cooperative behavior as in-role and extra-role behavior, and contract as a three-dimensional construct, including control, coordination and adaptati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…This approach enables firms to pay closer attention to all three functions of formal contracts to improve exchange efficiency. In related previous studies, Wang et al (2017) investigated the impact of contractual control, coordination, and adaptation on various aspects of relationships (such as prior interactions, standard levels of cooperative behavior, and voluntary cooperative behaviors) and Quanji et al (2016) investigated the relationships between contractual control, coordination, adaptation, and contractual partners' voluntary and obligatory cooperation. The two studies showed the usefulness of joint-contract functions in investigating cooperative behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…This approach enables firms to pay closer attention to all three functions of formal contracts to improve exchange efficiency. In related previous studies, Wang et al (2017) investigated the impact of contractual control, coordination, and adaptation on various aspects of relationships (such as prior interactions, standard levels of cooperative behavior, and voluntary cooperative behaviors) and Quanji et al (2016) investigated the relationships between contractual control, coordination, adaptation, and contractual partners' voluntary and obligatory cooperation. The two studies showed the usefulness of joint-contract functions in investigating cooperative behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of trusting relationships and incomplete contracts amongst various stakeholders involved in sustainable construction projects, many moral hazard behaviors, such as cutting corners and hiding defects, may remain hidden and unknown during the implementation of projects [25,26]. Although it is well documented in the literature that cooperation can enhance project benefits [27][28][29][30], quantitative approaches have not been common for exploring the effects of cooperation on the benefits of sustainable construction projects. The research object of this study is the cooperative Although it is well documented in the literature that cooperation can enhance project benefits [27][28][29][30], quantitative approaches have not been common for exploring the effects of cooperation on the benefits of sustainable construction projects.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is well documented in the literature that cooperation can enhance project benefits [27][28][29][30], quantitative approaches have not been common for exploring the effects of cooperation on the benefits of sustainable construction projects. The research object of this study is the cooperative Although it is well documented in the literature that cooperation can enhance project benefits [27][28][29][30], quantitative approaches have not been common for exploring the effects of cooperation on the benefits of sustainable construction projects. The research object of this study is the cooperative behavior between owners and contractors in sustainable construction projects.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the difficulty of collecting corresponding data sets from pairs of parties, future studies should consider this explorative route. Secondly, prior collaboration may relate to relational behavior and relationship quality, since prior interactions foster cooperative behavior (Wang, Chen, Fu, & Zhang, ). Researchers could explore how prior collaboration influences relational governance in the context of conflict through nuanced studies.…”
Section: Discussionmentioning
confidence: 99%